2014
DOI: 10.7883/yoken.67.432
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between BSG Polymorphisms and Cerebral Malaria

Abstract: SUMMARY:The Ok a blood group antigen basigin (BSG or CD147) is an erythrocyte receptor for the PfRh5 protein from Plasmodium falciparum. A recent study has shown that the PfRh5-BSG interaction is essential for erythrocyte invasion by P. falciparum. In this study, 6 SNPs in the BSG gene were investigated in 312 adult patients with P. falciparum malaria (109 cerebral malaria and 203 mild malaria patients) living in northwest Thailand. To examine the association between BSG SNPs and cerebral malaria, the allele a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
2
Order By: Relevance
“…Unexpectedly, we did not find any SNP that is directly related to the differential BSG expression, although Tham and coworkers reported that a specific SNP is responsible for the high or low CR1 expression. Another study showed that no BSG gene SNP correlated with susceptibility to malaria was observed . Likewise, this study did not observe any direct correlation between BSG gene polymorphism and OK/BSG level.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Unexpectedly, we did not find any SNP that is directly related to the differential BSG expression, although Tham and coworkers reported that a specific SNP is responsible for the high or low CR1 expression. Another study showed that no BSG gene SNP correlated with susceptibility to malaria was observed . Likewise, this study did not observe any direct correlation between BSG gene polymorphism and OK/BSG level.…”
Section: Discussioncontrasting
confidence: 74%
“…Another study showed that no BSG gene SNP correlated with susceptibility to malaria was observed. 17 Likewise, this study did not observe any direct correlation between BSG gene polymorphism and OK/BSG level. Nevertheless, this study found that posttranscriptional regulation might be involved in the BSG expression on RBCs.…”
Section: Discussioncontrasting
confidence: 59%
“…(13) . The Ok(a) blood group antigen basigin (BSG or CD147) is an erythrocyte receptor for the PfRh5 protein from Plasmodium falciparum and the PfRh5-BSG interaction is essential for erythrocyte invasion by Pf (14) . Anopheles stephensi mosquito, which is the main malaria vector in Iran, southwest Asia, and India, were fed either artificially on A/B/O/AB membrane blood feeders or directly on human volunteer hands and forearms of A/B/O/AB groups, under lab conditions.…”
Section: Discussionmentioning
confidence: 99%
“…BSG rs11473 polymorphism within miR-483-5p binding site was reported to be associated with increased risk of esophageal cancer in a Chinese population [29]. Other studies failed to demonstrate an association between BSG polymorphisms and risk of schizophrenia [30], cerebral malaria [31], and atherosclerotic cerebral infarction [32]. …”
Section: Discussionmentioning
confidence: 99%